Population Screening and Prevention Strategies for Thalassemias and other Hemoglobinopathies of Eastern India: Experience of 18, 166 cases. (2nd November 2015) - Chatterjee, Tridip; Chakravarty, Amit; Chakravarty, Sudipa
Abstract: We evaluated population screening programs (1999–2011), conducted by the Thalassaemia Foundation, Kolkata, India, for the first time in Eastern India in different districts of West Bengal, for prevention of thalassemia comprising screening of heterozygotes and β-thalassemia intermedia (β-TI) cases [β +, β ++, β 0 /β +, β E /β E (codon 26 or HBB : c.79G > A), Hb-E-β-thalassemia (Hb E-β-thal)]. Among 18, 166 cases, we found 2092 heterozygotes and 2245 β-TI individuals (who had no information about their disorders). Results were evaluated with standard hematological analyses including erythrocyte indices, hemoglobin (Hb) typing and quantification. Participants were divided into five groups (children, pre-marriage cases, pre-pregnancy cases, affected family members, pregnant women). The objectives of this evaluation were to fix cut-off values of red blood cells (RBCs), mean corpuscular volume (MCV), mean corpuscular Hb (MCH), red blood cell distribution width (RDW) and Hb A2, as the standard World Health Organization (WHO) guidelines were not strictly followed in mass-scale screening programs. We have observed many dilemmas in considering the status of the thalassemia subject, due to presence of some other clinical conditions such as iron deficiency anemia, α-thalassemia (α-thal), δ-thalassemia (δ-thal), clinically silent Hb variants, and some cases of non hemoglobinopathies (such as pregnancy) along with thalassemia. The MCV values varied greatly in different conditions of hemoglobinopathies, whereas MCH provided a more stable measurement. We found an MCH value of <27.0 pg is a suitable cut-off point for screening in this population. Participants with an MCH of <27.0 pg should be investigated further to confirm or exclude a diagnosis of β-thal trait.